Cochlear implant-specific risks should be considered, when assessing the quality of life of children and adolescents with hearing loss and cochlear implants–not just cochlear implant-specific benefits–Perspective - Huber, Maria (Frontiers in Neuroscience, 2022)
Cochlear implants (CIs) are electronic medical devices that enable hearing in cases where traditional hearing aids are of minimal or no use. Quality of life studies (QoL) of children and adolescents with a CI have so far focused on the CI-specific benefits. However, the CI-specific risks listed by the US Food and Drug Administration have not yet been considered. From this list, medical and device-related complications, lifelong dependency on the implanted device, and neurosecurity risks (CI technology is an interface technology) may be particularly relevant for young CI users. Medical and device-related complications can result in physical discomfort (e.g., fever, pain), functioning problems (e.g., in speech discrimination, social behavior, mood). In the worst case, reimplantation is required. Clinical experience shows that these complications are perceived as a burden for young CI users. Furthermore, many young patients are worried about possible complications. Additionally, CIs can be at least a temporary burden when children, typically at the age of 8 to 9 years, realize that they need the CI for life, or when they become peer victims because of their CI. With regard to the neurosecurity risks, it is still unknown, how young CI recipients perceive them. In summary, CI-specific risks can be perceived as a burden by young CI users that impairs their QoL. Therefore, they should not be ignored. There is an urgent need for studies on this topic, which would not only be important for professionals and parents, but also for the design of CI-specific QoL instruments.